Penguatan Keterampilan Mengajar Guru melalui Media Interaktif Canva Berbasis Kearifan Lokal dalam Pembelajaran Bahasa Indonesia di Sekolah Dasar - Novita Wulandari; Selvyanda Selvyanda; Riwan Jordan Perangin-angin; Nasrun Tumanggor; Nurmayani Nurmayani (Jurnal Merah Putih Sekolah Dasar, 2026)
The purpose of this study was to examine how Canva interactive media based on local wisdom is used in Indonesian language teaching in elementary schools and how it helps teachers become more proficient educators. This study used a descriptive design and qualitative methodology. Purposively selected elementary school teachers and students served as research subjects. Semi-structured interviews, documentation, and observation were used as data collection methods. To ensure data validity, triangulation techniques were applied during the data reduction, data presentation, and conclusion preparation stages. The findings indicate that incorporating local wisdom components into Canva interactive media can result in more engaging, dynamic, and contextual learning. This media improves teaching skills, particularly in the areas of pedagogical innovation, classroom management, and variety of learning approaches, by helping educators present content visually and methodically. Furthermore, because it relates to their cultural experiences, the incorporation of local wisdom increases student engagement and makes the subject matter more understandable. According to the study findings, Canva interactive media, based on local knowledge, is a successful educational innovation and helps Indonesian language teaching in elementary schools transition to meaningful, student-centered 21st-century learning.